Frequency of Autonomic Dysfunction in Patients with Guillain Barre Syndrome - Khalid, Sana; Aslam, Ayesha (Indus Journal of Bioscience Research, 2025)
Background and Aim: Guillain-Barre syndrome (GBS) described as a syndrome manifesting clinically as an acute inflammatory polyradiculoneuropathy (AIDP) with concomitant, symmetrical muscular weakness with absent or diminished deep tendon reflexes. Autonomic dysfunction (AD) is frequent and clinically important complication of GBS, which potentially contributes to adequate sickness and even mortality. The present study aimed to determine the frequency of AD in GBS patients. Patients and Method: This cross-sectional study investigated 100 patients presenting with new onset Guillain Barre Syndrome in the department of Neurology, Mayo Hospital, Lahore from October 2024 to April 2025. Patients aged 18-65 years of either gender presented with new onset GBS were enrolled.  Diagnosis of GBS was established through clinical assessment and supported by relevant investigations, including cerebrospinal fluid analysis and nerve conduction studies. Demographic information and illness duration recorded. All patients were evaluated for the presence of autonomic dysfunction (AD) using a standardized operational definition. Data analysis done using SPSS version 27. Results: The overall mean age was 37.82±4.62 years. Among the 100 patients diagnosed with Guillain-Barre syndrome, autonomic dysfunction (AD) seen in 38% of cases. The most common manifestations of AD included fluctuation in blood pressure (26%), cardiac arrhythmia (18%), and urinary retention (12%). AD seen more often in patients over 40 years of age and in patients with severe motor weakness. No significant gender-based differences in the frequency of AD observed. Conclusion: Autonomic dysfunction (AD) represents a frequent and significant complication in Guillain-Barre syndrome, affecting over one-third of affected individuals. Timely recognition and monitoring of autonomic symptoms are vital, as they play an important role in determining clinical outcomes and are associated with high risks of morbidity and mortality.